PENGARUH HARGA BI RATE, NILAI TUKAR RUPIAH, DAN INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Jalil, Abdul; Athoillah, Muhammad Hikam; Amaroh, Siti (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aims to determine the effect of the BI Rate, the rupiah exchange rate and inflation on the share prices of transportation sector companies on the Indonesian Stock Exchange 2020-2022. The approach in this research is quantitative. The data used is secondary data for the period 2020-2022. As for identifying data, use the help of eviews 10 to test panel data, by conducting a t (partial) test, f (simultaneous) test, and R2 test (coefficient of determination). Based on the t test (partial), the f (simultaneous) test Rate has no effect on transportation stock prices. The exchange rate has no effect on the transportation share price. Inflation has an influence on the price of transportation stocks. Based on the F test simultaneously the three variables have an effect on transportation stock prices.